Laser scanning microscopy of HTS films and devices(Review Article): Experimental Methods and Applications - Zhuravel, A.P.; Sivakov, A.G.; Turutanov, O.G.; Omelyanchouk, A.N.; Anlage, Steven M.; Lukashenko, A.; Ustinov, A.V.; Abraimov, D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The work describes the capabilities of laser scanning microscopy (LSM) as a spatially-resolved method of testing high–Tc materials and devices. The earlier results obtained by the authors are briefly reviewed. Some novel applications of the LSM are illustrated, including imaging the HTS responses in rf mode, probing the superconducting properties of HTS single crystals, development of two-beam laser scanning microscopy. The existence of the phase slip lines mechanism of resistivity in HTS materials is proven by LSM imaging.